2001
DOI: 10.1056/nejm200106213442503
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Glycoprotein IIb/IIIa Inhibition with Coronary Stenting for Acute Myocardial Infarction

Abstract: As compared with placebo, early administration of abciximab in patients with acute myocardial infarction improves coronary patency before stenting, the success rate of the stenting procedure, the rate of coronary patency at six months, left ventricular function, and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
328
6
25

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,049 publications
(371 citation statements)
references
References 32 publications
12
328
6
25
Order By: Relevance
“…43 Early administration of these agents, especially during the prehospital management phase, has been shown to improve coronary patency, with favourable trends for clinical outcome. 44 Importantly, a recent analysis obtained in a more homogeneous study population representative of modern primary PCI practice (n=1,101) [45][46][47] providing for the first time long-term follow-up to three years, confirmed a reduction in hard clinical outcomes with the use of GP IIb/IIIa receptor antagonists. This risk reduction translates into 50 major events (death or reinfarction) prevented for every 1,000 patients treated: this benefit increases five-fold in diabetics, with 250 deaths or MIs prevented for every 1,000 diabetic patients treated.…”
Section: Why Do Reperfusion Therapies Fail In Diabetics With Stemi?mentioning
confidence: 90%
“…43 Early administration of these agents, especially during the prehospital management phase, has been shown to improve coronary patency, with favourable trends for clinical outcome. 44 Importantly, a recent analysis obtained in a more homogeneous study population representative of modern primary PCI practice (n=1,101) [45][46][47] providing for the first time long-term follow-up to three years, confirmed a reduction in hard clinical outcomes with the use of GP IIb/IIIa receptor antagonists. This risk reduction translates into 50 major events (death or reinfarction) prevented for every 1,000 patients treated: this benefit increases five-fold in diabetics, with 250 deaths or MIs prevented for every 1,000 diabetic patients treated.…”
Section: Why Do Reperfusion Therapies Fail In Diabetics With Stemi?mentioning
confidence: 90%
“…On these bases, we suggest that, in these patients, the therapeutic strategies currently considered efficient in reducing mortality in acute myocardial infarction should be 6 1 9 used preferentially and early, being initiated in the emergency department 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 compares the results of the ISODATA technique with those of the ANN. As shown in this figure the lesion areas in the ISODATA maps are clustered to different signatures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Signatures range between one (corresponding to normal tissue) to twelve (corresponding to CSF or cavitated tissue).…”
Section: Resultsmentioning
confidence: 90%
“…Many studies, by correlating with follow-up imaging or neurological status, have shown the potential for diffusion weighted imaging (DWI), perfusion weighted imaging (PWI), and/or T 2 -weighted (T2WI) magnetic resonance imaging (MRI) used together for staging stroke outcome [3,7,8]. Most of these analyses were performed using as an outcome metric the volume of a region-of-interest (ROI) defined by the difference between an acute data set and the outcome image [9,10,11]. For instance, it has been shown that an unsupervised clustering technique such as ISODATA (Iterative Self-Organizing Data Analysis) can utilize combined MRI data sets from the acute phase [2,12] and the subacute phase [5] post-stroke to predict final infarct volume and thus produce a time-independent surrogate MRI outcome predictor [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%